The distribution of the Heavy Metals (Cu, Pb and Zn) in the Soft and Hard Tissues of the Green-Lipped Mussel Perna viridis (Linnaeus) Collected from Pasir Panjang, Peninsular Malaysia - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan; Abdul Rahim, Ismail (Universiti Putra Malaysia Press, 2007)
The distributions of Cu, Pb, and Zn in the different soft Pasir Panjang, Peninsular tissues, shell sections and layers of the green-lipped mussel Perna viridis from an area with unpolluted water in Malaysia, were studied.The soft tissues analysed were the byssus, mantle and gills,posterior adductor muscle, retractor byssal muscle, foot, crystalline style, gonad and the remaining visceral mass. The level of Cu in the crystalline style was significantly (P< 0.05) elevated when compared to the other soft tissues while elevated levels of Cu, Pb and Zn were found in the byssus. The byssus is therefore a more sensitive material for Cu, Pb and Zn. The heavy metal concentrations in the different sections of the mussel's shell layers were also differed. The level of Pb was significantly (P< 0.05) higher in the inner shell layer than in the inner shell layer. Copper, Pb and Zn were evenly distributed within the different sections of the inner shell layer with no significant (P< 0.05) difference in the concentrations of these metals in the different sections. The periostracum shell layer was found to be a more sensitive biomonitoring material for Cu, Pb and Zn than the inner shell layer.